Auditoría de gestión administrativa al sindicato de choferes del cantón Pujilí, provincia de Cotopaxi periodo del 1 de enero al 31 de diciembre del 2012 - Herrera Jácome, Carina Elizabeth (2014)
The present research was realized to evaluate the administrative process that maintains the Union of professional drivers of the Pujilí Canton, in the same way it is essential to measure the achieve of the objectives, and evaluate the stages of the administrative process because through them can check the efficiency and effectiveness with which the activities are carried out, the same one that allowed to analyses and interpret the results by giving importance to different factors that are incurred directly to the development of an organization. Specify if the activities are planned and what is the percentage of compliance, to obtain a real information and objective used different techniques of data collection such as: surveys, interviews, direct observation tests flash, there can detected some observations, for a better understanding of the results was carried out the analysis and interpretation of the results obtained. That research was a great contribution to the Union of drivers because of could find deficiencies that existing to achieve goals and objectives.